New horizons in web-based learning - ICWL 2010 workshops ICWL 2010 Workshops: STEG, CICW, WGLBWS, and IWKDEWL, Shanghai, China, December 7-11, 2010 Revised Selected Papers - Luo, Xiangfeng (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 9th International Conference on Web-Based Learning, ICWL 2010, held in Shanghai, China, in December 2010. The 36 revised full papers and 8 short papers presented were carefully reviewed and selected from 192 submissions. They deal with topics such as e-learning platforms and tools, technology enhanced learning, Web-based learning for oriental languages, mobile/situated e-learning, learning resource deployment, organization and management, design, model and framework of e-learning systems, e-learning metadata and standards, collaborative learning and game-based learning, as well as practice and experience sharing, and pedagogical issues.